2018
DOI: 10.1108/hff-01-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Coupled analysis of vehicle stability in crosswind on low adhesion road

Abstract: Purpose The purpose of this paper is to develop a two-way coupling approach for investigating the aerodynamic stability of vehicles under the combined effect of crosswind and road adhesion. Design/methodology/approach The author develops a new two-way coupling approach, which couples large eddy simulation with multi-body dynamics (MBD), to investigate the crosswind stability on three different adhesion roads: ideal road, dry road and wet road. The comparison of the results obtained using the traditional one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Safety, the perceived level of control and expected comfort in modern cars are reasons for the increased research focus on vehicle handling coupled to unsteady aerodynamics. Many studies available in the literature compare the effects of different aerodynamic features and investigate how to numerically couple aerodynamics and vehicle dynamics in a virtual environment [5][6][7][8]. However, few studies have investigated which aerodynamic and vehicle dynamic design parameters affect the sensitivity to crosswinds the most.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Safety, the perceived level of control and expected comfort in modern cars are reasons for the increased research focus on vehicle handling coupled to unsteady aerodynamics. Many studies available in the literature compare the effects of different aerodynamic features and investigate how to numerically couple aerodynamics and vehicle dynamics in a virtual environment [5][6][7][8]. However, few studies have investigated which aerodynamic and vehicle dynamic design parameters affect the sensitivity to crosswinds the most.…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines in the ISO 12021:2010 standard include a methodology where a vehicle is driven at 100 km/h into a zone of 20 m/s crosswind, resulting in a relative flow angle of ψ = 35.8 • (Figure 2 shows how the vehicle velocity, v x , and horizontal wind components, w x and w y , affect the relative flow magnitude, V mag , and angle, ψ). The resulting crosswind gust profile has been adopted in several numerical studies of crosswind sensitivity [5][6][7][8]17]. These extreme winds of 20 m/s create high aerodynamic forces and a distinct motion response of the vehicle, useful for measuring differences between vehicles and configurations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comprehensive consideration of the flow field around the vehicle and computational efficiency, the computational domain is created as a cuboid embracing the model. And, in view of reasonable results achieved in related references (Tien Phuc et al, 2015;Wang et al, 2017;Yang et al, 2017;Li et al, 2018), the inlet plane is placed at a distance of three times the body lengths ahead of the model, whereas the outlet plane is placed at seven times its length behind the model. The height and width of the computational domain is six times the body height and seven times the body width, respectively, which gives a blockage ratio of 2.64 per cent, and the blockage effect is eliminated according to the experimental studies in the HD-2 Wind Tunnel Laboratory.…”
Section: Windshiled Wipers Of Vehiclesmentioning
confidence: 68%
“…The real-time dynamic response and aerodynamic forces could be computed by the kinetics model and the aerodynamic model by using the two-way coupling method (Nakasato et al, 2017;Winkler et al, 2016;Wang et al 2020;Zhang et al 2020). At present, this approach has been used to analyse the aerodynamic performance and dynamic response of the vehicle in crosswinds (Huang et al, 2018;Li et al, 2018). The results demonstrated that the influence of the aerodynamic forces on the vehicle motion in the twoway coupling method is greater than that in the one-way coupling method.…”
Section: Introductionmentioning
confidence: 99%